Inclusive and Sustainable Development through Transformation, Innovation, and Digitalization in Nepal (Nepalese Journal of Management Research, 2025)
This research investigates the transformative impact of digital innovation on fostering inclusive and sustainable development in Nepal. By analyzing recent advancements and trends, the study highlights how digital technologies are bridging socioeconomic gaps, enhancing public service efficiency, and stimulating economic growth. The paper emphasizes the significance of digital literacy, robust infrastructure, and supportive policy frameworks in ensuring equitable access to digital resources. Through comprehensive case studies of successful digital initiatives and empirical data, the research underscores the role of digital transformation in achieving the Sustainable Development Goals (SDGs) and promoting a more inclusive society. Key findings include the importance of community engagement, public-private partnerships, and continuous capacity-building to sustain digital initiatives. Moreover, the study identifies critical challenges such as digital divide, cybersecurity concerns, and the need for adaptive governance. The findings indicate that strategic investments in digital infrastructure and capacity-building initiatives are essential for realizing Nepal’s development potential. The paper concludes by offering policy recommendations to foster an environment conducive to innovation and digitalization, ultimately contributing to the sustainable and inclusive growth of Nepal.